Is the physical activity environment surrounding primary schools associated with students' weight status, physical activity or active transport, in regional areas of Victoria, Australia? A cross-sectional study. Issue 7 (2nd July 2021) - Jacobs, Jane; Crooks, Nic; Allender, Steven; Strugnell, Claudia; Backholer, Kathryn; Nichols, Melanie
Abstract : Objectives: To explore whether the physical activity (PA) environment (walkability, greenspace and recreational facilities) surrounding regional primary schools is associated with children's PA levels, active transport and weight status. Limited research on this topic has been conducted outside of major cities. Design: Cross-sectional ecological study using baseline data from two large-scale obesity prevention interventions. Setting: Eighty (n=80) primary schools across two regional areas in Victoria, Australia. Participants: Students aged 8–13 years (n=2144) attending participating primary schools. Outcome measures: Measured weight status (body mass index z-score, proportion overweight/obese) and self-reported PA behaviours (meeting PA recommendations and active travel behaviour). Results: When adjusted for student and school demographics, students had significantly increased odds of using active transport to or from school when the school neighbourhood was more walkable (OR 1.21 (95% CI 1.09 to 1.35), had a greater number of greenspaces (OR 1.35 (95% CI 1.20 to 1.53)) and a greater number of recreational facilities (OR 1.18 (95% CI 1.07 to 1.31)). A higher cumulative PA environment score was also associated with a higher proportion of children using active transport (OR 1.33 (95% CI 1.28 to 1.51)). There were no significant associations between the PA environment measures and either weight status or meeting the PA recommendations in adjusted models. Conclusions: This study is the first of its kind exploring school neighbourhood environments and child weight status and PA in regional areas of Australia. It highlights the potential of the environment surrounding primary schools in contributing to students' active travel to and from school. Further research with the use of objective PA measurement is warranted in regional areas that have been under-researched. Trial registration number: Australian New Zealand Clinical Trials Registry (ANZCTR.org.au) identifier 12616000980437; Results.